Respostas
respondido por:
2
a) O perímetro será a soma dos lados do triângulo:
3x + 2y + 4 + 2x + y + 5 =
= 5x + 3y + 9.
b) Substituindo x por 3, e y por 4, temos que o perímetro é igual a:
5 · 3 + 3 · 4 + 9 =
= 15 + 12 + 9 =
= 27 + 9 =
= 36.
a) O perímetro será a soma dos lados do triângulo:
3x + 2y + 4 + 2x + y + 5 =
= 5x + 3y + 9.
b) Substituindo x por 3, e y por 4, temos que o perímetro é igual a:
5 · 3 + 3 · 4 + 9 =
= 15 + 12 + 9 =
= 27 + 9 =
= 36.
Perguntas similares
4 anos atrás
4 anos atrás
4 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás